Canal of Nuck Cyst vs. Inguinal Hernia: A Case Report and Further Considerations - Dionysios Prevezanos; Christos Doudakmanis; Stamatios Theocharis; Stylianos Kykalos; Nikolaos I. Nikiteas; Gerasimos Tsourouflis (Emergency Care and Medicine)
Background: Abnormalities in the canal of the Nuck are rare clinical entities with presentation in the early adulthood of females. Given their rarity, they can be misdiagnosed with a strangulated inguinal hernia. Methods: Herein, we report a young female with painful swelling of the right inguinal hernia and its surgical approach. Results: A 37-year-old female presented to the emergency department with pain in the right lower abdominal quadrant and an edematous inguinal mass. Physical examination showed a palpable inguinal mass, setting the suspicion for possible incarcerated inguinal hernia. Laboratory exams were within normal ranges. The patient was subsequently treated surgically. During the operation, a cystic well-rounded mass was identified and completely excised. The mesh and plug technique was the chosen technique for the restoration of the inguinal canal. The hospitalization length was one day, and the post-operative course was uneventful. Conclusions: Although a Nuck cyst is a rare entity, it should be taken into consideration in female adults who present with an inguinal mass.